Boarding House Rent Refunds During Covid 19 Based On Sharia Economic Law - Robi Musthofa Al Ghazali (Journal of Nusantara Economy, 2022)
This research discusses the issue of returning boarding fees for tenants who do not stay at their boarding houses during the Covid 19 pandemic. Apart from that, this research also discusses the review of Islamic Economic Law. This research is field research. Respondents to this study were village heads, boarding house owners and tenants. The collection techniques used were observation, documentation, and interviews. The findings of this study are that the boarding house owner provides compensation for the cost of renting a boarding house during the Covid-19 pandemic. According to Sharia Economic Law, the return of this rental fee is appropriate and fulfils several conditions and pillars of the rental contract. However, tenants were disappointed during the Covid 19 pandemic because the rent payments were the same as before the pandemic; the tenants' obligations continued to be carried out to pay the rent in full. The benefit rights obtained are not proportional to the payment in full. So, the practice of returning boarding house rent during a pandemic, according to Islamic economic law, is permissible as long as both parties are willing and do not harm both parties.   penelitian ini membahas persoalan pengembalian uang kos bagi penyewa yang tidak menepati kosannya pada masa pandemi covid 19, selain itu, penelitian ini juga membahas bagaimana Tinjauan Hukum Ekonomi Syariahnya. Penelitian ini adalah penelitian lapangan. Responden penelitian ini adalah kepala desa, pemilik Kosan dan Penyewa Kosan. Teknik pengumpulan yang digunakan adalah observasi, dokumentasi, dan interview. Temuan penelitian ini adalah pemilik kos memberikan despensasi terhadap biaya sewa kos selama masa pandemi covid 19. Menurut Hukum Ekonomi Syariah, pengembalian uang sewa ini sudah tepat dan memenuhi beberapa syarat dan rukun akad sewa menyewa. Namun, pada masa pandemi covid 19 di temukannya unsur kekecewaan oleh penyewa kerena pembayaran sewa sama dengan sebelum pandemi, kewajiban penyewa terus djalankan untuk membayar uang sewa kos secara penuh. hak manfaat di peroleh tidak sebanding dengan pembayaran secara penuh. Jadi, Praktik Pengembalian Uang Sewa Kos- kosa di Masa Pandemi Menurut Hukum Ekonomi Syariah di Perbolehkan selama kedua belah pihak rela dan tidak merugikan kedua belah pihak.